2016
DOI: 10.1049/hve.2016.0010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of field emission on microwave microdischarges

Abstract: An instability in the stable operation of microdischarges sustained at microwave frequencies, is investigated by a self-consistent one-dimensional particle-in-cell Monte Carlo collisions model. The instability is caused by the field electron emission from electrodes and is triggered by the high electric fields at the sheaths in a dense microplasma. For an operating frequency of 9 GHz, and electrode gap of 60 µm, the field emission (FE) is not active at the breakdown voltage. However, once a stable dense plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In air, the (pd) min predicted by Paschen's law is about 0.76 Torr cm [21]. The extremum of the gap distance d at atmospheric pressure is about ∼10 μm and the minimum breakdown voltage is V br,min ∼317 V. In the present needleto-plate configuration, the V br -d curve should be similar to that of the Paschen curve when d<10 μm.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In air, the (pd) min predicted by Paschen's law is about 0.76 Torr cm [21]. The extremum of the gap distance d at atmospheric pressure is about ∼10 μm and the minimum breakdown voltage is V br,min ∼317 V. In the present needleto-plate configuration, the V br -d curve should be similar to that of the Paschen curve when d<10 μm.…”
Section: Discussionmentioning
confidence: 60%
“…In fact, it is in Boyle and Kisliuk's paper [12] that the first 'schematic' of the modified Paschen curve was highlighted. Thereafter, a number of experiments have shown that a plateau appears on the V br -pd curve when the gap is less than 10 μm, followed by a continuous decrease in V br when d is further decreased [13][14][15][16][17][18][19][20][21][22][23]. In 1999 Torres and collaborators [24,25] presented evidence for the failure of Paschen's law, especially for the decrease in the breakdown voltage at decreasing gap.…”
Section: Introductionmentioning
confidence: 99%
“…However, in discharge voltage between 19 and 20 kV, the H 2 O 2 concentration increased rapidly with the discharge voltage rise, accompanied by the phenomenon of a much brighter plasma area and a rapid growth of discharge current, as shown in figure 5. The rapid growth indicated that postbreakdown of the gas gap happened in this interval with electronic avalanche [20]. Within this interval, many more hybrid discharges occurred at the interface of water droplets and oxygen, due to the rapidly increased discharge power, leading to an increased H 2 O 2 concentration.…”
Section: The Influence Of Applied Voltagementioning
confidence: 97%
“…Numerically and focusing on microwave microplasmas, most of the work performed has been focused either in one dimensional (1D) particle in cell (PIC) Monte Carlo models [26,33,34] or self-consistent 1D-two-dimensional (2D) fluid models in the quasi-static approximation [35,36]. Both 1D PIC and fluid simulations have provided important insight of breakdown voltages, frequency and field emission effects as well as spatial and temporal plasma evolution.…”
Section: Introductionmentioning
confidence: 99%